Advances in Quantum Dense Coding. Issue 5 (29th April 2019) - Guo, Yu; Liu, Bi‐Heng; Li, Chuan‐Feng; Guo, Guang‐Can
Abstract: Quantum dense coding is one of the most important protocols in quantum communication. It derives from the idea of using quantum resources to boost the communication capacity and now serves as a key primitive across a variety of quantum information protocols. This Progress Report focuses on the basic theoretical ideas behind quantum dense coding, discussing its development history from discrete and continuous variables to quantum networks, then to its variant protocols and applications in quantum secure communication. With this basic background in hand, then the main experimental achievements are reviewed, from photonic qubits and qudits to optical modes, nuclear magnetic resonance, and atomic systems. Besides the state of the art, finally potential future steps are discussed. Abstract : Quantum dense coding is one of the most important quantum information processes . In this protocol, people can transmit 2 log 2 d bits of classical information per every "qudit" information carrier use, at the cost of consuming pre‐shared entanglement. Many crucial aspects of dense coding, including the basic theory, extensions, and experimental achievements, are reviewed in this work.